2015
DOI: 10.1002/ccr3.196
|View full text |Cite
|
Sign up to set email alerts
|

STEC:O111‐HUS complicated by acute encephalopathy in a young girl was successfully treated with a set of hemodiafiltration, steroid pulse, and soluble thrombomodulin under plasma exchange

Abstract: Key Clinical MessageWe report a 14-year-old girl, who developed shigatoxin-producing E. coli (STEC)-HUS complicated by encephalopathy. She was successfully treated with hemodiafiltration, high-dose methylprednisolone pulse therapy, and soluble recombinant thrombomodulin under plasma exchange. von Willebrand factor multimers analysis provides potential insights into how the administered therapies might facilitate successful treatment of STEC-HUS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In our study, we found only one strain belonging to the addressed serogroups, corresponding to an O111 strain isolated from a pig. The detection of O111 strains in cattle and swine feces, as well as their association with severe illness in humans, is not surprising and was previously reported [70,71,72,73]. However, O111 STEC strains isolated from humans with moderate to severe illness are mainly associated with the presence of stx 1 type, together with eae and ehx A genes [72,73,74,75].…”
Section: Discussionmentioning
confidence: 77%
“…In our study, we found only one strain belonging to the addressed serogroups, corresponding to an O111 strain isolated from a pig. The detection of O111 strains in cattle and swine feces, as well as their association with severe illness in humans, is not surprising and was previously reported [70,71,72,73]. However, O111 STEC strains isolated from humans with moderate to severe illness are mainly associated with the presence of stx 1 type, together with eae and ehx A genes [72,73,74,75].…”
Section: Discussionmentioning
confidence: 77%
“…In this study, we observed that steroids or DAG analogues, which have been used in clinical medicine 37 or clinical trials 24 , have a suppressive effect on SubAB- or Stx-induced cytotoxicity. Stx is a major virulence factor that is responsible for severe gastrointestinal diseases caused by both LEE-positive and -negative STEC infections.…”
Section: Discussionmentioning
confidence: 78%
“…Recent studies showed that steroid pulse therapy was an effective treatment for severe STEC infection 18 , 37 . However, it remains unknown why steroids improve severe damage caused by STEC infection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, no brain imaging studies were done to assess the cause of somnolence, which may have been attributable to reversible encephalopathy, presumably resulting from increased vascular permeability. 17 However, the significance of the current report should be evaluated carefully with respect to several management concerns described below.…”
Section: Discussionmentioning
confidence: 99%